Controle de ferrugem asiática da soja utilizando produtos alternativos - Zorzzi, Ivan Carlos (2019)
In recent years, there has been a significant expansion of the organic market, driven primarily by new food consumption standards and new production standards adopted by producers. In this context, the main phytosanitary problem of soybean in the organic system is Asian rust (Phakopsora pachyrhizi), for which it is difficult to control, considering the restriction of products authorized for use in the organic system and the limitation of research related to this management system. The objective of this work was to evaluate the effect of alternative products on the germination of uredospores, on the severity of soybean rust on highlighted leaves and on the control of the disease under greenhouse and field conditions. The alternative treatments were calcium silicate, sulphocalcic and Bordeaux, and copper oxychloride. The variables analyzed were uredospores germination, disease severity, defoliation level, area under the disease progress curve (ABDPC), a thousand grain mass and productivity. The results indicate that there is a possibility of using copper oxychloride to handle Asian rust in organic production systems. Copper oxychloride reduced the germination of uredospores and when evaluated under controlled conditions using detached leaves and greenhouse reduced the severity of the disease. In field conditions, copper oxychloride at the doses of 588 and 882 g ha-1 reduced severity and ABDPC, in addition to increasing productivity at 1434 kg ha-1 in relation to the control. It is concluded that copper oxychloride can be used as a tool in the management of Asian rust in organic systems of soy production.